New Developments in Respiratory Support for Preterm Infants - Jain, Deepak; Bancalari, Eduardo (American Journal of Perinatology, 2019)
The evolution of neonatal respiratory support has been one of the cornerstones for the advancements in neonatal–perinatal medicine, allowing survival of infants previously considered not viable. There is an increasing focus on developing strategies which are not only lifesaving but also minimize lung and other organ systems injury, thereby reducing long-term morbidities. Respiratory support immediately after birth is an area that had lagged behind in terms of evidence base and technological advancements until recently. Some of these advancements include use of a respiratory function monitors for measuring flow and tidal volume, new evidence for oxygen supplementation and monitoring, and the efforts to formulate an ideal strategy for establishing functional residual capacity after birth. Increasing evidence for the benefits of avoiding invasive ventilation on reduction of bronchopulmonary dysplasia has resulted in efforts to further reduce the need for endotracheal intubation by applying newer strategies such as less invasive surfactant instillation, noninvasive high-frequency oscillatory ventilation, or use of high flow nasal cannula oxygen. For infants requiring mechanical ventilation, newer strategies such as volume targeted ventilation or neurally adjusted ventilation are being evaluated to reduce ventilator induced lung injury. Despite these advances, there are significant challenges, including lack of conclusive evidence base for many of currently used respiratory strategies, no reduction in the incidence of bronchopulmonary dysplasia in the last decade, and difficulties in defining outcome measures that better reflect long-term respiratory health.
Keywords: respiratory support; preterm infant; endotracheal Intubation